Terpenoids and Coumarin from Bursera serrata Wall. - Ara, Kulsum; Rahman, Mohammad S; Rahman, AHMM; Hasan, Choudhury M; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Two terpenoids, β-amyrin (1) and β-sitostenone (2) and a coumarin, scopoletin (3) were isolated from petroleum ether and dichloromethane soluble extracts of the stem bark of Bursera serrata Wall. The structures of the isolated compounds 1-3 were established by extensive spectroscopic studies as well as by comparison with published data. Although compounds 1-3 have been isolated from various plant species previously, this is the first report of the occurrence of these compounds from B. serrata. The crude extractives exhibited weak antimicrobial activity and cytotoxicity. Key words: Bursera serrata; Burseraceae; β-amyrin; β-sitostenone; scopoletin; antimicrobial; cytotoxicity DOI: 10.3329/dujps.v8i2.6023 Dhaka Univ. J. Pharm. Sci. 8(2): 107-110, 2009 (December)